Evaluation of residual stresses in CO2 laser beam welding of SS316L weldments using FEA. (1st January 2023) - Vemanaboina, Harinadh; Babu, M Mohan; Prerana, Inguva Chinmaya; Gundabattini, Edison; Yelamasetti, Balram; Saxena, Kuldeep K; Salem, Karrar Hazim; Khan, Muhammad Ijaz; Eldin, Sayed M; Agrawal, Manoj Kumar
Abstract: Laser welding is used in critical component production when tight tolerances like minimal distortions and residual stresses are required. Laser beam welding offers a lower heat input, a smaller heat affected zone, lower residual stresses, minimum distortions, and greater mechanical joint characteristics than conventional welding does. In order to simulate the laser welding process used on SS316L plates, the Gaussian heat source model was used. The model is developed and simulated with volumetric heat source model with APDL coding using ANSYS. The thermal profiles at the joint cross sections via welded area, interface across joints is taken for the analysis. The maximum temperature was observed at the fusion zone and associated zones. The residual stresses are analysed in the same path and found the stresses are in safe limits of base material. Predicted and experimentally measured residual stresses are close agreement with 10%.